Immigration and new firm formation: Evidence from a quasi-experimental setting in Germany - Vera Jahn; Max Friedrich Steinhardt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
This paper analyzes in how far immigration affects firm formation at the regional level. For this purpose, we exploit a placement policy in Germany in the 1990s for immigrants of German origin from Eastern Europe and the former Soviet Union. Our panel regressions suggest that immigration had a positive impact on regional firm formation. The most likely mechanisms driving this result are labor supply-side effects and positive implications of cultural diversity. Overall, our paper demonstrates that immigration induced changes in local labor supply can partially be absorbed by the creation of firms. – – Die Studie analysiert inwieweit Zuwanderung Firmengründungen in einer Region beeinflusst. Die empirische Analyse bezieht sich hierbei auf Aussiedler - ethnische Deutsche, die primär auf dem Gebiet der ehemaligen Sowjetunion lebten und in den 1990er und 2000er Jahren bei ihrer Einreise nach Deutschland einer bestimmten Region zugewiesen wurden. Unsere Panel-Regressionen deuten darauf hin, dass sich die besagte Zuwanderung positiv auf regionale Firmengründungen ausgewirkt hat. Die wahrscheinlichsten Mechanismen hinter diesem Ergebnis sind arbeitsangebotsseitige Effekte sowie positive Auswirkungen kultureller Vielfalt. Insgesamt zeigt unser Papier, dass zuwanderungsbedingte Veränderungen des lokalen Arbeitsangebots teilweise durch Unternehmensgründungen aufgefangen werden können.
Keywords: F22; L26; R11; 330; immigration; placement policy; economic impact; firms